Upaya Guru Dalam Menanamkan Pendidikan Karakter Di TPQ Al-Huda Desa D. Tegalrejo Kecamatan Tugumulyo Kabupaten Musi Rawas - Fitriyani, Fitriyani; Astuti, Rika Astuti; Darmayani, Dwi Shinta; Prasetio, Riki Dwi; Krisna, Titing (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
Character education is a process to instill character values ​​in students so that they have good personalities and can determine how to think, behave and act in making decisions to live and work together in the family, community, nation and state. This research is motivated by the decline in the morale of the Indonesian people, especially the next generation of the nation with the occurrence of crime and brawls with the perpetrators, mostly young people. TPQ Al-Huda as a non-formal education becomes an effective institution to instill character values ​​in students from an early age. This research was conducted with the aim of knowing the teacher's efforts in instilling character education in students. This study uses a qualitative research type with a descriptive approach. For data collection tools, researchers used the method of observation, interviews and documentation to obtain data which was then analyzed to obtain conclusions. From the results of data analysis, it can be concluded that teachers instill character education values ​​through the methods of habituation, reprimand and example. The values ​​of character education are instilled through teaching and learning activities such as reading and writing the Qur'an, memorizing prayers and short letters, guidance in the field of faith and morals. This can be seen from the attitudes and behavior of students such as polite, friendly, gentle, honest, independent, disciplined and responsible.